They call me Sacagawea - Hunsaker, Joyce Badgley (Two Dot Books, 2003)
They Call Me Sacagawea is rich and classic storytelling. The history of the astounding expedition of Lewis and Clark leaps off the page when told here by their teenage Shoshone interpreter--Sacagawea. Readers learn about this young mother's extraordinary travels with the celebrated Corps of Discovery and gain detailed insight into native traditions and life ways through unforgettable images and a beautifully presented story based on oral traditions, scholarly research, and historical anecdotes.